Pay for performance in the pool: Sink or swim? - Harris, J. S.; Dulin, J. (Journal of Sports Economics, 2024)
In the shadow of Title IX's 50th anniversary in 2022, it is fitting to investigate whether female elite swimmers are rewarded the same way male swimmers are. This article thus contributes to the growing literature on gender differences in performance and pay in sport. Our article frames this question in a unique way, as we compare the extent of economic exploitation of women and men in elite swimming. Are female swimmers "underpaid" relative to their marginal revenue products at the same level as their male counterparts?